2019
DOI: 10.1002/cne.24743
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic modulation of olfactory‐evoked motor output in sea lampreys (Petromyzon marinus L.)

Abstract: Detection of chemical cues is important to guide locomotion in association with feeding and sexual behavior. Two neural pathways responsible for odor‐evoked locomotion have been characterized in the sea lamprey (Petromyzon marinus L.), a basal vertebrate. There is a medial pathway originating in the medial olfactory bulb (OB) and a lateral pathway originating from the rest of the OB. These olfactomotor pathways are present throughout the life cycle of lampreys, but olfactory‐driven behaviors differ according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Second, in the ventral hypothalamus, a potential homolog to A11 comprises periventricular DA‐positive neurons projecting to the spinal cord (Barreiro‐Iglesias et al, 2008), but not to the mesencephalic locomotor region (Ryczko et al, 2013). Third, DA‐positive neurons of the dorsal hypothalamus project to the olfactory bulb, but their homolog in mammals is unresolved (Beauséjour et al, 2020). Fourth, DA‐positive neurons in the lamprey olfactory bulb are likely homolog to A16 (Beauséjour et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, in the ventral hypothalamus, a potential homolog to A11 comprises periventricular DA‐positive neurons projecting to the spinal cord (Barreiro‐Iglesias et al, 2008), but not to the mesencephalic locomotor region (Ryczko et al, 2013). Third, DA‐positive neurons of the dorsal hypothalamus project to the olfactory bulb, but their homolog in mammals is unresolved (Beauséjour et al, 2020). Fourth, DA‐positive neurons in the lamprey olfactory bulb are likely homolog to A16 (Beauséjour et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…First, lamprey DA neurons located in the posterior tuberculum, a ventral diencephalic region, share similarities with mammalian A8–A10 DA neurons. These DA‐positive neurons project up to the striatum (Ericsson et al, 2013; Pombal, El Manira, & Grillner, 1997; Robertson et al, 2012; Ryczko et al, 2013; Stephenson‐Jones, Samuelsson, Ericsson, Robertson, & Grillner, 2011; von Twickel et al, 2019), olfactory bulb (Beauséjour et al, 2020), or down to the mesencephalic locomotor region (Ryczko et al, 2013), optic tectum (inferior colliculus in mammals, von Twickel et al, 2019), but not to the spinal cord (Ryczko et al, 2013). Some DA neurons contain glutamate and send functional glutamatergic inputs to their targets (Ryczko et al, 2017; von Twickel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalences between these prosocial centers in mice with lamprey centers have yet to be reported, and the social life of lampreys is poorly known. Interestingly, the lamprey striatum, as the mouse medial amygdala, receives secondary olfactory projections [45,54], which might be important in mature adults for feeding, reproduction and mate choosing [55]. Recent studies of the olfactory system in the sea lamprey revealed two olfactory pathways via the medial and non-medial parts of the olfactory bulb that project toward the posterior tubercle and motor centers, and to the lateral pallium, respectively [56,57], but a direct relation of these medial and non-medial pathways with the striatum has yet to be deciphered.…”
Section: Discussionmentioning
confidence: 99%
“…The SNc/VTA also receives sensory information from multiple areas. Olfactory information reaches the SNc/VTA from both the medial olfactory bulb [ 46 ], a projection shown to contribute to locomotion [ 47 , 48 ], and from the main olfactory bulb [ 49 ]. Visual inputs reach the SNc/VTA from the tectum (homologue of the mammalian superior colliculus; SC), as well as the pretectum [ 3 , 8 , 50 ].…”
Section: The Snc/vta At the Base Of Vertebrate Evolutionmentioning
confidence: 99%